Experimental and analytical investigation on the coupled elastoplastic damage model of coal-rock: The investigation on damage model of coal-rock (Fracture and Structural Integrity, 2020)
In this paper, a novel coupled elastoplastic damage model for coal-rock is proposed to predict the deformation and potential disaster in coal mining. The conditions of small deformation and thermodynamic potential are considered, as well as the coupling of damage evolution process with the plastic deformation and the plastic hardening of coal-rock. Based on the theory of damage mechanics, the formulas of damage evolution, plastic yield and plastic potential of coal-rock are deduced theoretically. In addition, triaxial compression tests of coal-rock under the different confining stresses are conducted to reveal the law of deviatoric stress and strain. Based on the experimental data, the control parameters of the coupled elastoplastic damage model of coal-rock are determined. The theoretical results obtained from the coupled elastoplastic damage model for coal-rock agree well with those from the experiment. The proposed model is reasonable to predict the deformation of coal-rock.
Keywords: Coal-rock; Coupled elastoplastic damage model; Damage mechanics; Triaxial compression tests; The deformation prediction of coal-rock